Good Outcome Following Copeland Hemiarthroplasty for Acromegalic Arthropathy - S. E. Johnson-Lynn; J. Candal-Couto (Case Reports in Orthopedics)
We report the unusual case of a patient with acromegalic arthropathy who presented with severe shoulder arthrosis with marked osteophytosis. This patient is currently pain-free and has good shoulder function 4 years following a Copeland shoulder hemiarthroplasty. Acromegaly is a rare condition of growth hormone oversecretion, but arthropathy is a common feature of the natural history of the disease. This is the first published case report of the outcome of shoulder arthroplasty in a patient with acromegalic arthropathy and demonstrated that a good result can be obtained in this patient.